ISO 14000 - Namen okoljskega standarda in njegove posledice - Praznik, Miha (Strojniški vestnik, 2000)
Business survival of company in the modern world, marked with international trade, depends on many economic factors, such as free, cross-border trade and competition under same conditions. Trading with products and services without trade barriers is a request of every producer and supplier. Standards are connected to trade for a long time. Their use makes trading with products and services easier, and so it's accepted by sellers and buyers. Standards like ISO 9000 (quality standard) and ISO 14000 (environmental standard) contribute to higher quality of trade in modern world of global trading. The paper discusses the family of international environmental management standards ISO 14001 with European Union regulation EMAS and presents the certification according to ISO 14001.
Keywords: ISO 14000; ISO 14001; ISO 9000; ENEM; upravljanje z okoljem; vplivi na okolje; natural environment; okolje; ecology; ekologija; ekološka politika; kvaliteta; zagotavljanje kvalitete; standardi; ISO 14000 standardi; ISO 14001 standardi; ISO 9000 standardi